1994
DOI: 10.1038/ki.1994.363
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear leukocytes increase glomerular albumin permeability via hypohalous acid

Abstract: Acute glomerulonephritis is characterized by the presence of neutrophils within glomeruli and the generation of reactive oxygen species (ROS) by activated polymorphonuclear leukocytes (PMNs). Hydrogen peroxide (H2O2) and other ROS including hypothalous acids have been implicated in PMN mediated injury. To determine the role of specific ROS in PMN mediated glomerular injury, isolated rat glomeruli were incubated for 30 minutes at 37 degrees C with H2O2, with H2O2 and myeloperoxidase, or with activated PMNs. Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…This study demonstrated a functional pathogenic role of endogenous MPO in kidney damage during experimental neutrophilmediated GN. MPO is involved in the generation of a variety of injurious reactive intermediates, including HOCl, which has been shown to induce glomerular damage in vitro (39), and ROS, such as the hydroxyl radical and singlet oxygen (7). Previous studies showed that neutrophils contribute to glomerular injury by ROS production (40).…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated a functional pathogenic role of endogenous MPO in kidney damage during experimental neutrophilmediated GN. MPO is involved in the generation of a variety of injurious reactive intermediates, including HOCl, which has been shown to induce glomerular damage in vitro (39), and ROS, such as the hydroxyl radical and singlet oxygen (7). Previous studies showed that neutrophils contribute to glomerular injury by ROS production (40).…”
Section: Discussionmentioning
confidence: 99%
“…(ii) a de crease in Ln after 60 min and (iii) an increase in Polbumin. The increase in Paibumin by PAF is less in magnitude than the in crease seen after treatment with superoxide, hydroxyl ion or during injury with antibody and complement [27][28][29], Mechanisms by which PAF might decrease GFR include increased renal vascular resistance, contraction of mesangi al cells and decreased filtering capillary area and/or de crease in Lp. The current studies document that PAF acts on the glomerulus in at least two ways to cause a decrease in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…The assay reflects injury to the glomerular protein permeability barrier and is not specific to FSGS serum/ plasma. For example, agents as diverse as TNF␣, superoxide, or antibodies to protein tyrosine phosphatase receptor and ␤1 integrin increase P alb (42)(43)(44)(45)(46). Sera from some but not all patients with FSGS cause increased P alb in isolated glomeruli.…”
Section: Permeability Factors In Fsgs and Posttransplant Recurrencementioning
confidence: 99%